"Make me feel special": Are hierarchical loyalty programs a panacea for all brands? The role of brand concept. (September 2017) - Mimouni Chaabane, Aida; Pez, Virginie
Abstract: Despite extant literature, the most effective structure of loyalty programs is still heavily questioned among researchers. Building on the congruence principle, we examine the moderating role of brand concept. Our findings reveal that for symbolic brand concepts, customers perceive hierarchical loyalty program structures (which classify customers into tiers according to spending levels or other purchase activities) to be more congruent; this perception increases firm loyalty intentions. However, for functional brand concepts, customers perceive hierarchical and linear loyalty programs structures as equally congruent. Also for symbolic brand concepts, program structure appears as the most important feature in ensuring perceived congruence between a program and a brand, ahead of program benefits. These findings have important theoretical and managerial implications.